Knowledge and behavior towards oral lichen planus: An observational study - WEHBÉ, Hiam; NEHMÉ, Edgard (International Arab Journal of Dentistry (IAJD), 2019)
Lichen planus is an immunologically mediated mucocutaneous disease that is triggered by multiple etiological agents. Oral lichen planus (OLP) is characterized by a slow evolution without complete remission, nor spontaneous healing. The establishment of an early diagnosis is essential to be able to support and to relieve patients with oral lichen plan lesions especially those in active phase. This requires recognition by the dentists of the signs and symptoms, characteristics and different clinical forms under which this pathological entity may occur. The purpose of our survey was to evaluate the knowledge of dentists (teachers and Master students) in the Faculty of Dental Medicine of Saint Joseph University, Beirut, on the oral lichen planus by means of a survey study.